2011
DOI: 10.1299/jsdd.5.429
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Feed-Forward Control Design Approaches for Flexible Multibody Systems

Abstract: End-effector trajectory tracking of flexible multibody systems is a challenging task. In this paper feed-forward control designs based on quasi-static deformation compensation and exact model inversion for end-effector trajectory tracking are presented. They are combined with a simple feedback strategy and tested by simulation of a very flexible two arm manipulator. With both approaches good results for end-effector trajectory tracking are obtained. It is shown that a significant improvement of the inverse mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Similar linearly combined outputs are also often used in end-effector tracking of flexible manipulators, see e.g. De Luca (1998); Seifried et al (2011). For this rotational arm the servo-constraint is given by…”
Section: Illustrative Example 2: Rotational Manipulator Armmentioning
confidence: 98%
See 2 more Smart Citations
“…Similar linearly combined outputs are also often used in end-effector tracking of flexible manipulators, see e.g. De Luca (1998); Seifried et al (2011). For this rotational arm the servo-constraint is given by…”
Section: Illustrative Example 2: Rotational Manipulator Armmentioning
confidence: 98%
“…Analysis of 124 R. Seifried and W. Blajer: Analysis of servo-constraint problems for underactuated multibody systems such systems are given e.g. in Seifried (2012b) and Seifried et al (2011), respectively.…”
Section: Illustrative Example 2: Rotational Manipulator Armmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper addresses the inverse dynamics of non-minimum phase underactuated multibody systems, which represent an important class of practical applications. For example, nonminimum phase behavior can occur when joint actuators are used to control the end effector of a flexible manipulator [23] or a manipulator with passive joints [20]. The inverse dynamics of a non-minimum phase system is known to be non-causal, which means that the control forces and torques should start before the beginning of the trajectory (pre-actuation phase) and continue after the end-point is reached (post-actuation phase).…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, for a given system output y the inverse model provides the control input for exact output reproduction. For flexible manipulators it is often possible to define a simplified linearly combined system output y = q r + Γ Γ Γq e to approximate the end-effector position bŷ r ef (y) ≈ r ef (q r , q e ), see [1]. It can be shown that flexible manipulators in end-effector trajectory tracking in many cases have vector relative degree {2, · · · , 2}, while often the internal dynamics is unbounded, i.e.…”
mentioning
confidence: 99%